Let's solve the equation step-by-step to determine how many solutions it has:
Given the equation: \[ 5(2x + 2) - 7x = 3x + 6 \]
-
Distribute on the left side: \[ 10x + 10 - 7x = 3x + 6 \]
-
Combine like terms: \[ 3x + 10 = 3x + 6 \]
-
To isolate the variable, subtract \(3x\) from both sides: \[ 10 = 6 \]
This statement is a contradiction because 10 does not equal 6.
Since we arrived at a contradiction, this indicates that the equation has no solution.
Thus, the final response would be: The equation has no solution.